YouTube Sebagai Media Intervensi Edukasi Kesehatan Reproduksi: Dampaknya Terhadap Pengetahuan Siswa - Sutrisno Papayungan; Muhammad Edward; A. Muh. Akbar (YICI Publisher, 2025)
Sexuality issues such as premarital sex among teenagers, risky sexual behavior, and abortion at a young age occur due to the low knowledge of teenagers about reproductive health. The presence of adolescent reproductive health education with the selection of effective methods is expected to improve knowledge about reproductive health. Research Objective: To determine the effect of providing education through YouTube media on the level of knowledge of adolescents about reproductive health at SMK Kristen Makale. Research Method: This research is a pre-experimental study using a one-group pre-test and post-test design conducted in June - July 2023. The sample for this study consisted of students from SMK Kristen Makale, randomly selected with a sample size of 50 individuals. Data were analyzed using descriptive statistical analysis and inferential statistical analysis. The research results concluded that there was an increase in students' knowledge about reproductive health after receiving educational intervention through YouTube.